An innovative modular device and wireless control system enabling thermal and pressure sensors using FPGA on real-time fault diagnostics of steam turbine functional deterioration. (1st March 2018) - Devi, S.; Saravanan, M.
Graphical abstract: Highlights: Continuous measurement of five process parameters and calculation of two performance indices with respect to time. Storage in databases based on their power generation. Data collection and fault request. Fault detection and diagnosis using VLSI based FPGA hardware. This arrangement provides a good functional framework to detect the root causes. Abstract: It is necessary that the condition of the steam turbines is continuously monitored on a scheduled basis for the safe operation of the steam turbines. The review showed that steam turbine fault detection and operation maintenance system (STFDOMS) is gaining importance recently. In this paper, novel hardware architecture is proposed for STFDOMS that can be communicated through the GSM network. Arduino is interfaced with the FPGA so as to transfer the message. The design has been simulated using the Verilog programming language and implemented in hardware using FPGA. The proposed system is shown to be a simple, cost effective and flexible and thereby making it suitable for the maintenance of steam turbines. This system forewarns the experts to access to data messages and take necessary action in a short period with great accuracy. The hardware developed is promised as a real-time test bench, specifically for investigations of long haul effects with different parameter settings.